Optimal Monetary Poily and Finansial stability in Iran (VAR under Policy Approach) - Hossein Bastanzad; Pedram Davoudi (مدلسازی اقتصادسنجی, 2019)
Financial stability is firmly considred as a supplementary goal in the monetary policy environment post 2007 financial crisis. New monetary policy that contains monetary thriple goals -price stability, sustainable growth and financial stability- in the context of optimum policy rule is highly recommended post crisis although some policymakers are still interested in utilizing the convetional approach based on discretionary measures given the restrictions in macroeconomic structural spcification. In this regard, a Vector Auto Regression under Policy (PVAR) approach is technically applied as an alternative approach to resolve the specification challenge. The PVAR approach is also utilized to estimate monetary policy optimum reaction function given the financial stability. The model output indicate that the policy reaction function significantly affcets the triple goals so policymaker reaction function reduces price and financial instability along with more sustabible growth.